Image forming device

JP2025022532APending Publication Date: 2025-02-14SHARP KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023127209
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0017】 本開示の画像形成装置によれば、現像剤の使用初期における現像剤の急速な帯電量変化を抑えることで、長期にわたって画像濃度及びその均一性に優れる、長期にわたってカブリの発生を抑制することができる等、優れた効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022532000001_ABST
    Figure 2025022532000001_ABST
Patent Text Reader

Abstract

To provide an image forming device that has excellent image density and excellent image density uniformity and can suppress occurrence of fogging for a long term by restraining a rapid change in the amount of electrification of developer in an initial stage of use of the developer.SOLUTION: An image forming device in which a two-component developer composed of an initial toner and a carrier is filled into a development tank in advance, and a replenishment toner is replenished into the development tank as development progresses has the following configuration. The initial toner contains a fine powder body in which the surface of a core in which silica is added to strontium titanate is subjected to hydrophobization treatment with a silane compound, and a silica particle as external additives, and does not contain any titanium dioxide particles or contains a titanium dioxide particle with a mass content of 50% or smaller of the fine powder body. The replenishment toner contains a titanium dioxide particle and a silica particle as external additives, and does not contain any fine powder bodies or contains the fine powder bodies with a mass content of 50% or smaller of the titanium dioxide particle.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an image forming apparatus. [Background technology]

[0002] In image forming devices using electrophotography, such as copying machines, multifunction machines, printers, and facsimile machines, a toner image is generally formed by attaching toner to an electrostatic latent image formed on the surface of a photoconductor. The amount of toner used to form the toner image moves from the developing tank to the photoconductor, and an amount of toner corresponding to that amount is replenished from the toner cartridge to the developing tank. Toner particles with external additives attached to their surfaces are generally used, as shown in FIG. 2.

[0003] The developer filled in the developer tank generally loses a large amount of charge at a relatively early stage when the developer is first used due to stirring stress in the developer tank. Therefore, in order to ensure the amount of charge required for the developer to form an appropriate image at the stage when the product life has progressed, it is considered effective to add a charge control agent with high charge stability, such as titanium dioxide (titanium(IV) oxide) particles, as an external additive to the toner.

[0004] Patent Document 1 discloses that in a developing method in which an electrostatic latent image formed on the surface of a photoconductor is developed with a toner, a hollow-out preventing agent is added to an initial toner (toner in a developer filled in advance in a developing tank) while no hollow-out preventing agent is added to a replenishment toner (toner for replenishment), the hollow-out preventing agent is at least one selected from the group consisting of metal soap, titanium dioxide, strontium titanate, and strontium oxide, and fine powder of zinc stearate is used as the metal soap. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 8-314280 Summary of the Invention [Problem to be solved by the invention]

[0006] However, if a toner is designed to ensure an appropriate charge amount at the end of the developer's product life while taking into account the decrease in charge amount at the beginning of developer use, it is unavoidable to design the toner so that the charge amount at the beginning of developer use is high (see "High charge toner" in Figure 7), which creates issues such as insufficient image density at the beginning of use and increased change in image color due to large changes in charge amount.

[0007] Furthermore, when the external additives are different between the initial toner and the replenishment toner (when different types of external additives are used), problems generally arise in that the initial toner and the replenishment toner are not mixed well, which can lead to problems such as reduced uniformity of image density (problems of color unevenness occurring in the image) and problems such as the occurrence of fogging. Note that fogging refers to the phenomenon in which toner is developed in non-image areas where toner is not normally developed.

[0008] The image forming apparatus disclosed herein has been developed in consideration of such circumstances, and its main objective is to provide an image forming apparatus that can suppress the occurrence of fogging and has excellent image density and uniformity over a long period of time by suppressing rapid changes in the charge amount of a developer in the early stages of use. [Means for solving the problem]

[0009] The image forming apparatus disclosed herein, which has been made to solve the above problems, is an image forming apparatus in which a two-component developer consisting of an initial toner and a carrier is filled in a developing tank in advance, and a replenishment toner is replenished into the developing tank as development is performed. The initial toner and the replenishment toner are toners having external additives attached to the surfaces of the toner particles. The initial toner contains, as external additives, fine powder in which the surface of a core made of strontium titanate to which silica has been added is hydrophobized with a silane compound, and silica particles, and does not contain titanium dioxide particles or contains titanium dioxide particles at a mass content of 50% or less of the fine powder. The replenishment toner contains, as external additives, titanium dioxide particles and silica particles, and does not contain the fine powder or contains the fine powder at a mass content of 50% or less of the titanium dioxide particles.

[0010] In the above image forming apparatus, it is preferable that the molar ratio of silicon atoms to titanium atoms in the fine powder is 0.03 or more and 1.00 or less.

[0011] In addition, in the above-mentioned image forming apparatus, it is preferable that the content of the fine powder per 100 parts by mass of toner particles in the initial toner is 0.3 parts by mass or more and 1.5 parts by mass or less, and that the content of titanium dioxide particles per 100 parts by mass of toner particles in the replenishment toner is 0.3 parts by mass or more and 1.5 parts by mass or less.

[0012] In addition, in the above-mentioned image forming apparatus, when the content of the fine powder per 100 parts by mass of toner particles in the initial toner is A parts by mass, and the content of titanium dioxide particles per 100 parts by mass of toner particles in the replenishment toner is B parts by mass, it is preferable that BA is 0.3 or less.

[0013] In addition, in the above-mentioned image forming apparatus, it is preferable that the volume average particle diameter of the toner particles in the initial toner and the replenishment toner is 4 μm or more and 9 μm or less, and the average primary particle diameter of the fine powder and titanium dioxide particles in the initial toner and the replenishment toner is 20 nm or more and 60 nm or less.

[0014] In addition, in the above-mentioned image forming apparatus, it is preferable that the silica particles contained as an external additive in the initial toner and the replenishment toner are composed of first silica particles having an average primary particle diameter of 20 nm or less and second silica particles having an average primary particle diameter of 80 nm or more and 150 nm or less.

[0015] In addition, in the above-mentioned image forming apparatus, it is preferable that the content of silica particles per 100 parts by mass of toner particles in the initial toner is 1.5 parts by mass or more and 3.0 parts by mass or less, and that the content of silica particles per 100 parts by mass of toner particles in the replenishment toner is 1.5 parts by mass or more and 3.0 parts by mass or less.

[0016] In the above image forming apparatus, it is preferable that, in the initial toner, the adhesion strength of the fine powder and titanium dioxide particles to the toner particles is X(Ti), and the adhesion strength of the silica particles to the toner particles is X(Si), and that X(Si) / X(Ti) is 1.1 or less. In the replenishment toner, it is preferable that, in the fine powder and titanium dioxide particles to the toner particles is Y(Ti), and that Y(Si) / Y(Ti) is 1.1 or less. Effect of the Invention

[0017] According to the image forming apparatus of the present disclosure, by suppressing the rapid change in charge amount of the developer in the initial stage of use, excellent effects can be achieved, such as excellent image density and uniformity over a long period of time and suppression of the occurrence of fogging over a long period of time. [Brief description of the drawings]

[0018] [Figure 1] 2 is a schematic diagram showing a toner particle surface of an initial toner according to the present embodiment. FIG. [Diagram 2] 1 is a schematic diagram illustrating a toner particle surface of a general low-charge toner. [Diagram 3] 5A and 5B are schematic diagrams illustrating replacement of toner in a developing tank in the image forming apparatus according to the present embodiment. [Figure 4] 1 is a schematic diagram illustrating the replacement of toner in a developing tank when a general low-charge toner is used as the initial toner and a general high-charge toner is used as the replenishment toner; FIG. [Diagram 5] 6 is a graph illustrating the relationship between the stirring time and the charge amount in the image forming apparatus according to the present embodiment. [Figure 6] 5 is a graph illustrating the relationship between the stirring time and the charge amount in the case of FIG. 4. [Figure 7] 1 is a graph illustrating the relationship between the stirring time and the charge amount when low-charge and high-charge toners are used alone; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The image forming apparatus of the present disclosure will be described in detail below. First, the characteristics of the image forming apparatus as a whole will be described, and then the raw materials constituting the initial toner and the replenishment toner will be described.

[0020] 1. Image forming equipment In the image forming apparatus according to this embodiment, a two-component developer composed of an initial toner and a carrier is filled in a developer tank in advance, and replenishment toner is replenished into the developer tank as development is performed.

[0021] The initial toner and replenishment toner used in the image forming apparatus according to this embodiment are toners having external additives attached to the surfaces of the toner particles. The initial toner contains, as external additives, "fine powder in which the surface of a core made of strontium titanate to which silica has been added is hydrophobized with a silane compound" (hereinafter, this fine powder is also simply referred to as "fine powder") and silica particles, and does not contain titanium dioxide particles or contains titanium dioxide particles at a mass content of 50% or less of the fine powder. The replenishment toner contains, as external additives, titanium dioxide particles and silica particles, and does not contain fine powders or contains fine powders at a mass content of 50% or less of the titanium dioxide particles.

[0022] By using the initial toner as described above, the charge amount of the initial toner can be designed to be relatively low compared to the case where a toner containing a large amount of titanium dioxide particles as an external additive is used as the initial toner, and the charge amount of the developer at the beginning of use of the developer (hereinafter also referred to as the beginning of printing) becomes appropriate. In addition, by using the replenishment toner as described above, the charge amount of the replenishment toner can be designed to be relatively high, and the charge amount of the developer at the stage where the product life has progressed can be maintained high. According to the image forming device according to the present embodiment, which is a combination of such initial toner and replenishment toner, image defects such as color unevenness, density reduction, and line width change can be suppressed for a long period of time, and high-quality images can be formed.

[0023] The "fine powder obtained by hydrophobizing the surface of a core made of strontium titanate with silica by a silane compound" has a rounded cubic shape, and by adding (attaching) it to the surface of a toner particle, the frictional force during toner flow is increased. As a result, when an initial toner to which this fine powder is attached is mixed with a replenishment toner to which highly fluid particles such as titanium dioxide particles are added to the surface, the toner is easily stirred uniformly. In addition, a difference in charge occurs between the initial toner and the replenishment toner, which have different external additives. As a result, electrostatic attraction occurs during stirring, making it easier to stir more uniformly. FIG. 3 is a schematic diagram for explaining the replacement of toner in a developing tank in an image forming apparatus according to this embodiment. As shown in Figure 3, according to the configuration of this embodiment, when a two-component developer consisting of initial toner T1 and carrier C is replenished with replenishment toner T2 and stirred in a developing tank, the initial toner T1 and replenishment toner T2 tend to be uniformly dispersed and present as shown on the right side of Figure 3, so that the initial toner T1 and replenishment toner T2 are developed in a balanced manner, and ultimately it is possible to form high-quality images over a long period of time.

[0024] In contrast, FIG. 4 is a schematic diagram for explaining the replacement of toner in a developing tank when a general low-charge toner is used as the initial toner and a general high-charge toner is used as the replenishment toner. For example, when a toner with a spherical shape and a low-charge charge control agent attached to the toner particle surface is used as the initial toner T11, the dissociation from the carrier C surface becomes too high, and when replenishment toner T12 with titanium dioxide particles attached to the toner particle surface is replenished, the replacement of the toner attached to the carrier C surface (replacement from the initial toner to the replenishment toner) progresses rapidly, causing a problem of uneven charge in the developer. Therefore, as shown in FIG. 4, the developed toner is biased, and as a result, there is a problem of image defects such as a decrease in uniformity of image density (unevenness in image density occurs within the same surface). In addition, when a general low-charge toner and a high-charge toner are combined in this way, uneven charge occurs in the developer, so that the transition of the charge of the developer becomes unstable as shown in FIG. 6, and there is a problem of image defects such as an increase in color change of the image due to a large change in charge.

[0025] In the image forming apparatus according to the present embodiment, the initial toner contains, as an external additive, "fine powder obtained by hydrophobizing the surface of a core made of strontium titanate with silica added thereto with a silane compound," which has a certain degree of irregularity, and therefore the initial toner has a strong frictional force, and is therefore likely to be retained to a certain degree on the carrier surface. As a result, the initial toner is replaced by the replenishment toner at an appropriate speed, so that even if there is a difference in charge amount between the initial toner and the replenishment toner, it is possible to suppress the occurrence of unevenness in the charge amount in the developer, and as shown in Figure 5, the change in the charge amount of the developer is stable (the charge amount change has a small gradient), and it is possible to form high-quality images over a long period of time.

[0026] 2. Toner particles The initial toner and replenishment toner according to the present embodiment are toner particles (toner cores) having external additives attached to their surfaces. The toner particles according to the present embodiment are composed of internal additives such as colorants, release agents, and charge control agents, and binder resins, and the internal additives are dispersed in the binder resins. If necessary, any optional components may be contained within a range that does not impair the effects of the present disclosure. The volume average particle diameter of the toner particles in the initial toner and replenishment toner is, for example, 3 μm or more and 10 μm or less, preferably 4 μm or more and 9 μm or less, and more preferably 5 μm or more and 8 μm or less. If the volume average particle diameter of the toner particles is less than the lower limit, the adhesion force between the toner and the carrier increases significantly, making it difficult for the initial toner to be replaced by the replenishment toner, and the uncharged toner may cause fogging. If the volume average particle diameter of the toner particles exceeds the upper limit, the adhesion force between the toner and the carrier weakens, and the replacement of the initial toner with the replenishment toner proceeds rapidly, which may reduce the uniformity of the image density (cause unevenness in the image density).

[0027] <Binding resin> The toner particles constituting the initial toner and the replenishment toner according to the present embodiment contain a binder resin. The binder resin is not particularly limited, and resins used in the field of electrophotography can be used, for example, polyester resins, polystyrene resins such as styrene-acrylic resins, (meth)acrylic acid ester resins, polyolefin resins, polyurethane resins, and epoxy resins. These resins may be used alone or in combination of two or more. Among these, polystyrene resins and polyester resins are preferred, and polyester resins are particularly preferred.

[0028] As the polystyrene resin, styrene-acrylic resin (styrene-acrylic copolymer resin) is preferable, and as the styrene monomer usable as the resin raw material, for example, styrene derivatives such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, etc. As the acrylic monomer, for example, acrylic acid derivatives and methacrylic acid derivatives such as acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, propyl acrylate, octyl acrylate, 2-chloroethyl acrylate, phenyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, phenyl methacrylate, dimethylamino methacrylate, etc. are mentioned.

[0029] Furthermore, vinyl monomers such as maleic anhydride, maleic acid monomethyl ester, maleic acid monoethyl ester, maleic acid monophenyl ester, maleic acid monoallyl ester, and divinylbenzene may be used as the resin raw material.

[0030] The polyester resin used in the binder resin is usually obtained by polycondensation reaction of one or more selected from a dihydric alcohol component and a trihydric or higher polyhydric alcohol component with one or more selected from a divalent carboxylic acid and a trihydric or higher polycarboxylic acid by a known method via an esterification reaction or an ester exchange reaction.

[0031] The conditions for the polycondensation reaction may be appropriately set depending on the reactivity of the monomer components, and the reaction may be terminated when the polymer has suitable physical properties. For example, the reaction temperature is about 170° C. to 250° C., and the reaction pressure is about 5 mmHg to normal pressure.

[0032] Examples of the dihydric alcohol component include alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane; Examples of the diols include glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; bisphenol A; propylene adducts of bisphenol A; ethylene adducts of bisphenol A; and hydrogenated bisphenol A.

[0033] Examples of trihydric or higher polyhydric alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, sucrose (cane sugar), 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.

[0034] In the toner particles according to the present embodiment, one of the dihydric alcohol components and the trihydric or higher polyhydric alcohol components may be used alone, or two or more of them may be used in combination.

[0035] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, cyclohexanedicarboxylic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, n-dodecylsuccinic acid, n-octylsuccinic acid, isooctenylsuccinic acid, isooctylsuccinic acid, and acid anhydrides and lower alkyl esters thereof.

[0036] Examples of trivalent or higher polyvalent carboxylic acids include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, and acid anhydrides and lower alkyl esters thereof.

[0037] In the toner particles according to the present embodiment, one of the divalent carboxylic acids and trivalent or higher polyvalent carboxylic acids may be used alone, or two or more of them may be used in combination.

[0038] The weight average molecular weight of the polyester resin is preferably 3000 or more and 50000 or less. If the weight average molecular weight is less than the lower limit, the peelability on the high temperature side of the fixable region (non-offset region) may be deteriorated. On the other hand, if the weight average molecular weight exceeds the upper limit, the low temperature fixability may be deteriorated.

[0039] The polyester resin preferably has an acid value of 5 mgKOH / g or more and 30 mgKOH / g or less. If the acid value is less than the lower limit, the electrostatic chargeability of the polyester resin decreases, and the electrostatic control agent becomes difficult to disperse in the polyester resin, which may adversely affect the electrostatic rise property and the electrostatic stability during continuous printing. On the other hand, if the acid value exceeds the upper limit, the electrostatic chargeability may become unstable due to high hygroscopicity.

[0040] <Internal additives> -wax- The toner particles according to the present embodiment may contain a wax as a release agent. As the wax, waxes used in the field of electrophotography may be used, for example, paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, polypropylene wax, carnauba wax, synthetic ester wax, etc. These waxes may be used alone or in combination of two or more. The content of the wax in the toner particles is preferably 0.5% by mass or more and 10% by mass or less.

[0041] -Coloring agent- The toner particles according to the present embodiment may contain a colorant. As the colorant, organic pigments, organic dyes, inorganic pigments, inorganic dyes, and the like used in the field of electrophotography can be used.

[0042] Examples of black colorants include carbon black, copper oxide, manganese dioxide, aniline black, activated carbon, non-magnetic ferrite, magnetic ferrite, and magnetite.

[0043] Examples of yellow colorants include CI Pigment Yellow 12, CI Pigment Yellow 13, CI Pigment Yellow 14, CI Pigment Yellow 15, CI Pigment Yellow 17, CI Pigment Yellow 74, CI Pigment Yellow 93, CI Pigment Yellow 94, CI Pigment Yellow 138, CI Pigment Yellow 180, and CI Pigment Yellow 185.

[0044] Examples of magenta colorants include CI Pigment Red 48:1, CI Pigment Red 53:1, CI Pigment Red 57:1, CI Pigment Red 122, CI Pigment Red 123, CI Pigment Red 139, CI Pigment Red 144, CI Pigment Red 149, CI Pigment Red 166, CI Pigment Red 177, CI Pigment Red 178, and CI Pigment Red 222.

[0045] Examples of cyan colorants include CI Pigment Blue 15, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 16, CI Pigment Blue 60, and the like.

[0046] The content of the colorant in the toner particles is preferably 3 parts by mass or more and 10 parts by mass or less. The colorant may be used in the form of a master batch in order to disperse it uniformly in the binder resin.

[0047] -Charge control agent- The toner particles according to the present embodiment may contain a charge control agent. The charge control agent is added to impart a preferable chargeability to the toner. The charge control agent is not particularly limited, and charge control agents for positive charge control and negative charge control used in the field of electrophotography can be used.

[0048] Examples of charge control agents for controlling positive charges include quaternary ammonium salts, pyrimidine compounds, triphenylmethane derivatives, guanidine salts, and amidine salts.

[0049] Charge control agents for negative charge control include metal-containing azo compounds, azo complex dyes, metal complexes and metal salts of salicylic acid and its derivatives (metals include chromium, zinc, zirconium, etc.), organic bentonite compounds, and boron compounds.

[0050] These charge control agents may be used alone or in combination of two or more. The content of the charge control agent in the toner particles is preferably 0.5% by mass or more and 5% by mass or less.

[0051] 2.External additives The initial toner according to the present embodiment contains, as external additives, fine powder and silica particles, and does not contain titanium dioxide particles or contains titanium dioxide particles at a mass content of 50% or less of the fine powder. More preferably, the initial toner according to the present embodiment contains, as external additives, fine powder and silica particles, and does not contain titanium dioxide particles.

[0052] The replenishment toner according to the present embodiment contains titanium dioxide particles and silica particles as external additives, and does not contain fine powder or contains fine powder at a mass content of 50% or less of the titanium dioxide particles. More preferably, the replenishment toner according to the present embodiment contains titanium dioxide particles and silica particles as external additives, and does not contain fine powder.

[0053] The fine powder in which the surface of a core made of strontium titanate to which silica has been added is hydrophobized with a silane compound can be produced, for example, by the following procedures (1) to (5).

[0054] (1) Metatitanic acid obtained by the sulfuric acid method is desulfurized and bleached, then desulfurized by adding an aqueous solution of sodium hydroxide, and then neutralized with hydrochloric acid, filtered, and washed with water to obtain a washed cake. (2) Water is added to the washed cake to make a slurry, and then hydrochloric acid is added to perform a peptization process. This is solution 1, and is mixed with solution 2, an aqueous solution of strontium chloride, and solution 3, an aqueous solution of sodium silicate. The mixing ratio of solutions 1, 2, and 3 is set so that the molar ratio of (Sr+Si) / Ti is 1.2. (3) Heat the mixed solution to 90°C under a nitrogen gas atmosphere, add an aqueous sodium hydroxide solution and stir for 2 hours to complete the reaction. (4) After the reaction, the slurry is cooled to 50°C, hydrochloric acid is added and stirred for 2 hours. The resulting precipitate is washed, separated by filtration, and then dried. (5) The dried product is ground in a blender for 1 minute, and the coarse powder is removed using a sieve with a mesh size of 32 μm. The resulting fine powder base material (core) is then surface-coated with a silane coupling agent. Examples of methods for surface coating with a silane coupling agent include surface treatments commonly used in the art using hexamethyldisilazane (HMDS), dimethyldichlorosilane (DDS), octylsilane (OTAS), polydimethylsiloxane (PDMS), etc.

[0055] As in this manufacturing example, when the surface of a core made of strontium titanate with added silica is hydrophobized with a silane compound, the particles become relatively spherical, have improved dispersibility and flowability, and are less abrasive than a core without added silica.

[0056] The molar ratio Si / Ti of silicon atoms to titanium atoms in the fine powder is preferably 0.03 to 1.00, more preferably 0.03 to 0.10. The molar ratio Si / Ti represents the content of silica in the fine powder. If the molar ratio Si / Ti is less than the lower limit, the shape of the fine powder is angular, so that the adhesion between the carrier and the toner becomes too strong, and the toner is not mixed well with the replenishment toner, which may reduce the uniformity of the image density (unevenness in the image density occurs within the same surface). If the molar ratio Si / Ti exceeds the upper limit, the negative chargeability of the fine powder increases, which may cause a decrease in the image density at the initial stage of printing.

[0057] The titanium dioxide particles may be anatase type titanium dioxide particles or rutile type titanium dioxide particles. For example, as described in JP-A-2000-10335, a method for producing anatase type titanium dioxide particles includes a method for obtaining titanium dioxide particles by hydrolyzing and granulating a solution in which a raw material such as ilmenite ore is dissolved in sulfuric acid, drying, and then firing at a high temperature. For example, as described in JP-A-2001-26423, a method for producing rutile type titanium dioxide particles includes a method for obtaining titanium dioxide particles by hydrolyzing an aqueous titanium tetrachloride solution to prepare a fine titania sol having a rutile nucleus, separating the titania sol, and then heat treating the resulting solution to obtain titanium dioxide particles. The surface of the titanium dioxide particles may be hydrophobized, and examples of the hydrophobization include a treatment for surface coating with a silane coupling agent. Examples of the method for surface coating with a silane coupling agent include surface treatments commonly used in the technical field using hexamethyldisilazane, dimethyldichlorosilane, octylsilane, polydimethylsiloxane, etc.

[0058] In the image forming apparatus according to the present embodiment, the content of the fine powder relative to 100 parts by mass of toner particles in the initial toner is preferably 0.3 parts by mass or more and 1.5 parts by mass or less, more preferably 0.7 parts by mass or more and 1.3 parts by mass or less. The content of the titanium dioxide particles relative to 100 parts by mass of toner particles in the replenishment toner is preferably 0.3 parts by mass or more and 1.5 parts by mass or less, more preferably 0.7 parts by mass or more and 1.3 parts by mass or less. If the content of the fine powder in the initial toner or the content of the titanium dioxide particles in the replenishment toner is less than the lower limit, the charge amount of the toner may be too high, and good image quality may not be obtained both at the beginning of printing and after continuous printing. If the content of the fine powder in the initial toner or the content of the titanium dioxide particles in the replenishment toner exceeds the upper limit, the charge amount of the toner may be too low, and fogging may easily occur both at the beginning of printing and at the end of the product life.

[0059] In the image forming apparatus according to the present embodiment, when the content of fine powder per 100 parts by mass of toner particles in the initial toner is A parts by mass, and the content of titanium dioxide particles per 100 parts by mass of toner particles in the replenishment toner is B parts by mass, it is preferable that BA is 0.3 or less, If BA exceeds the upper limit, the difference in charge between the initial toner and the replenishment toner becomes large, and the change in charge between the initial printing stage and the end of the product life stage becomes too large, which may result in increased color change during continuous printing.

[0060] The average primary particle diameter of the fine powder and titanium dioxide particles in the initial toner and the replenishment toner is preferably 20 nm or more and 60 nm or less, more preferably 25 nm or more and 50 nm or less. If the average primary particle diameter of the fine powder or titanium dioxide particles is less than the lower limit, the toner fluidity increases and the difference in fluidity between the initial toner and the replenishment toner decreases, which may cause the initial toner to be rapidly replaced by the replenishment toner, resulting in uneven image density. If the average primary particle diameter of the fine powder or titanium dioxide particles exceeds the upper limit, the toner fluidity decreases and the difference in fluidity between the initial toner and the replenishment toner increases, which may cause the image to become rough. Note that "rough" refers to a state in which the image quality is non-uniform and has a rough feel.

[0061] The silica particles contained as an external additive in the initial toner and the replenishment toner according to the present embodiment are preferably composed of first silica particles (small silica particles) having an average primary particle diameter of 20 nm or less and second silica particles (large silica particles) having an average primary particle diameter of 80 nm or more and 150 nm or less. The first silica particles more preferably have an average primary particle diameter of 15 nm or less, and the second silica particles more preferably have an average primary particle diameter of 90 nm or more and 130 nm or less. If the average primary particle diameter of the first silica particles exceeds the above upper limit, the flowability of the toner may decrease, causing roughness in the image and unevenness in the image density. If the average primary particle diameter of the second silica particles is less than the above lower limit, the durability of the toner may decrease, causing roughness in the image as the product life progresses. If the average primary particle diameter of the second silica particles exceeds the above upper limit, the flowability of the toner may decrease, causing roughness in the image and unevenness in the image density.

[0062] In the image forming apparatus according to the present embodiment, the content of silica particles relative to 100 parts by mass of toner particles in the initial toner is preferably 1.5 parts by mass or more and 3.0 parts by mass or less, more preferably 2 parts by mass or more and 2.8 parts by mass or less. The content of silica particles relative to 100 parts by mass of toner particles in the replenishment toner is preferably 1.5 parts by mass or more and 3.0 parts by mass or less, more preferably 2 parts by mass or more and 2.8 parts by mass or less. If the content of silica particles in the initial toner or the replenishment toner is less than the lower limit, the durability of the toner decreases, and as the product life progresses, there is a risk of image roughness and fogging occurring. If the content of silica particles in the initial toner or the replenishment toner exceeds the upper limit, the adhesion strength of the fine powder and titanium dioxide particles to the toner particles decreases, and these external additives are more likely to cause carrier contamination by transferring (adhering) to the carrier, so that as the product life progresses, the charge amount decreases and fogging is more likely to occur.

[0063] In the image forming apparatus according to the present embodiment, if the adhesion strength of the fine powder and titanium dioxide particles to the toner particles in the initial toner is X(Ti) and the adhesion strength of the silica particles to the toner particles is X(Si), then X(Si) / X(Ti) is preferably 1.1 or less, and more preferably 1 or less. If the adhesion strength of the fine powder and titanium dioxide particles to the toner particles in the replenishment toner is Y(Ti) and the adhesion strength of the silica particles to the toner particles is Y(Si), then Y(Si) / Y(Ti) is preferably 1.1 or less, and more preferably 1 or less. If the adhesion strength ratio X(Si) / X(Ti) or Y(Si) / Y(Ti) exceeds the upper limit, carrier contamination is likely to progress, and the charge amount decreases as the product life progresses, which may make fogging more likely to occur.

[0064] 3. Two-component developer, carrier The two-component developer according to the present embodiment is composed of a toner and a carrier. The two-component developer pre-filled in the developing tank of the image forming apparatus according to the present embodiment is composed of an initial toner and a carrier. The two-component developer can be produced by mixing the toner and the carrier using a known mixer. The mass ratio of the toner to the carrier is not particularly limited, and may be, for example, 3:97 to 12:88.

[0065] The carrier is stirred and mixed with the toner in the developing tank, giving the toner a desired charge. The carrier also acts as an electrode between the developing device and the photoconductor, carrying the charged toner to the electrostatic latent image on the surface of the photoconductor to form a toner image. The carrier is held on the developing roller of the developing device by magnetic force, and after acting in development, it returns to the developing tank, where it is stirred and mixed with new toner again and is used repeatedly until the end of its life.

[0066] The carrier preferably has a carrier core material and a resin coating layer that coats the carrier core material. The carrier core material is not particularly limited as long as it is used in the electrophotographic field. Examples of materials that constitute the carrier core material include magnetic metals such as iron, copper, nickel, and cobalt; and magnetic metal oxides such as ferrite and magnetite. The volume average particle size of the carrier core material is not particularly limited, but is preferably 30 μm or more and 100 μm or less. The resin coating layer preferably contains a silicone resin or an acrylic resin. Silicone resin can delay the progression of contamination of the carrier coat layer, and is suitable for long-life use. EXAMPLES

[0067] The image forming apparatus of the present disclosure will be specifically described below based on examples and comparative examples. First, various measurement methods and evaluation methods will be described.

[0068] <Measurement method> -Method for measuring the volume average particle size of toner particles- 20 mg of toner particles and 1 ml of sodium alkyl ether sulfate were added to 50 ml of electrolyte (Beckman Coulter, Inc., product name: ISOTON-II), and the mixture was dispersed for 3 minutes at a frequency of 20 kHz using an ultrasonic disperser (As One Corporation, tabletop dual-frequency ultrasonic cleaner, model: VS-D100) to obtain a measurement sample. The obtained measurement sample was measured using a particle size distribution measuring device (Beckman Coulter, Inc., model: Multisizer3) under the conditions of aperture diameter: 100 μm, measurement particle number: 50,000 counts, and the volume average particle size was calculated from the volume particle size distribution of the sample particles.

[0069] -Method for measuring adhesive strength of external additives- The adhesion strength of each external additive to the toner particles was measured by the following procedure. (1) 2.0 g of toner is added to 40 ml of a 0.2% by mass aqueous solution of Triton (polyoxyethylene octylphenyl ether), and the mixture is stirred for 1 minute. (2) Using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., model: US-300T), irradiate the above aqueous solution with ultrasonic waves (output: 40 μA, 4 minutes). (3) The aqueous solution after the ultrasonic irradiation is left to stand for 3 hours, and the toner and the liberated external additives are separated. (4) After removing the supernatant, add approximately 50 ml of pure water to the precipitate and stir for 5 minutes. (5) The mixture is subjected to suction filtration using a membrane filter having a pore size of 1 μm (manufactured by Advantec Co., Ltd.). (6) The toner remaining on the filter is vacuum dried overnight. (7) Using an X-ray fluorescence analyzer (Rigaku Corporation, model: ZSX Primus II), the intensities of elements (Si and Ti) in the external additives contained in 1 g of toner before and after the series of processes (1) to (6) above are analyzed, and the adhesion strength of each external additive is calculated using the following formula.

[0070] Adhesion strength of external additives containing silicon [%] = {(Si strength after treatment) / (Si strength before treatment)} × 100 (I) Adhesion strength of external additives containing Ti [%] = {(Ti strength after treatment) / (Ti strength before treatment)} × 100 (II)

[0071] Specifically, in the initial toner, the adhesion strength X(Ti) of the fine powder and titanium dioxide particles to the toner particles is calculated by the above formula (II), and the adhesion strength X(Si) of the silica particles to the toner particles is calculated by the above formula (I). Similarly, in the replenishment toner, the adhesion strength Y(Ti) of the fine powder and titanium dioxide particles to the toner particles is calculated by the above formula (II), and the adhesion strength Y(Si) of the silica particles to the toner particles is calculated by the above formula (I).

[0072] - Image density evaluation method - The prepared developer and toner were filled into the developing device and toner cartridge of a color multifunction printer (manufactured by Sharp Corporation, model: MX-8081), respectively. Next, a continuous printing test was performed on 2000 sheets of A4 paper in an environment of a temperature of 25°C and a humidity of 50%, so that a square solid image with a side length of 10 mm was formed at three positions, namely, the center and both ends in the axial direction of the developing roller. The first printed sheet was taken as the first printed sample, and the 2000th printed sheet was taken as the second printed sample. The image density was measured at 10 arbitrary positions for the first and second printed samples, and the average value was calculated.

[0073] Based on the calculated average image density, the image was evaluated according to the following criteria. ◎(Excellent): The average image density is 1.45 or more. ◯ (Good): The average image density is 1.30 or more and less than 1.45. △(Acceptable): The average image density is 1.15 or more and less than 1.30. × (unacceptable): The average image density is less than 1.15.

[0074] - Method for evaluating uniformity of image density - The prepared developer and toner were filled into the developing device and toner cartridge of a color multifunction printer (manufactured by Sharp Corporation, model: MX-8081), respectively. Next, a continuous printing test was performed on 2000 sheets of A4 paper in an environment of a temperature of 25°C and a humidity of 50%, so that a square solid image with a side length of 10 mm was formed at three positions, namely, the center and both ends in the axial direction of the developing roller. The first printed sheet was taken as the first printed sample, and the 2000th printed sheet was taken as the second printed sample. The image density was measured at 10 arbitrary positions for the first and second printed samples, and the standard deviation of the image density was calculated. A larger standard deviation indicates lower uniformity.

[0075] Based on the calculated standard deviation, the evaluation was made according to the following criteria. ◎ (Excellent): Standard deviation is less than 0.1. ○ (Good): The standard deviation is 0.1 or more and less than 0.2. △ (Acceptable): The standard deviation is 0.2 or more and less than 0.4. × (Fail): The standard deviation is 0.4 or more.

[0076] -How to evaluate fogging- To measure the fog value, an image is printed in which 10% of the printable area of ​​A4 paper is filled with toner, and a color difference meter (manufactured by Nippon Denshoku Industries Co., Ltd., model: ZE6000) is used to measure the brightness of specific areas of the image that are not filled in. The difference between this brightness and the brightness measured before printing is taken as the fog value.

[0077] The prepared developer and toner were filled into a developing device and a toner cartridge of a color multifunction printer (Model: MX-8081, manufactured by Sharp Corporation), respectively. Next, a continuous printing test was performed in which the above image was printed on 2000 sheets of A4 paper in an environment of a temperature of 25°C and a humidity of 50%, and the first printed sheet was taken as the first printed sample, and the 2000th printed sheet was taken as the second printed sample.

[0078] The fog values ​​of the first and second print samples were measured, and the fog was evaluated according to the following criteria. ◎(Excellent): The fogging value is less than 1.4. ◯ (Good): The fog value is 1.4 or more and less than 1.7. △(Fair): The fog value is 1.7 or more and less than 2.0. × (Fail): The fogging value is 2.0 or more.

[0079] <Preparation of toner raw materials> -Preparation of fine powder- Metatitanic acid obtained by the sulfuric acid method was bleached to remove iron, and then desulfurized by adding an aqueous sodium hydroxide solution. It was then neutralized with hydrochloric acid, filtered, and washed to obtain a washed cake. Water was added to the washed cake to make a slurry, and hydrochloric acid was added to perform a peptization treatment. This was called solution 1, and solution 1 was mixed with solution 2, an aqueous strontium chloride solution, and solution 3, an aqueous sodium silicate solution. The mixing ratio of solutions 1, 2, and 3 was set so that the molar ratio of (Sr+Si) / Ti was 1.2. This mixed solution was heated to 90°C under a nitrogen gas atmosphere, and stirred for 2 hours while adding an aqueous sodium hydroxide solution to complete the reaction. The slurry after the reaction was cooled to 50°C, hydrochloric acid was added, and stirred for 2 hours. The precipitate obtained after stirring was washed, separated by filtration, and then dried. This dried material was pulverized in an air flow mill, and the coarse powder was removed using a sieve. The fine powder base material (core) obtained was then surface-coated with octylsilane to obtain a "fine powder in which the surface of a core made of strontium titanate with added silica has been hydrophobized with a silane compound."

[0080] According to the above procedure, "Fine Powder 1" to "Fine Powder 10" were prepared, which have different molar ratios of silicon atoms to titanium atoms (Si / Ti) and average primary particle sizes in the fine powder. The physical properties of "Fine Powder 1" to "Fine Powder 10" are shown in Table 1 below.

[0081] [Table 1]

[0082] -Preparation of titanium dioxide particles- Ilmenite ore was dissolved in sulfuric acid to separate iron powder, and TiO(OH)2 was obtained by a wet precipitation method to hydrolyze TiOSO4. In the process of obtaining TiO(OH)2, dispersion adjustment and washing for hydrolysis and nucleation were performed. Next, 20 parts by mass of isobutyltrimethoxysilane was dropped into 1000 ml of water in which 100 parts by mass of the obtained TiO(OH)2 was dispersed, while stirring at room temperature. Next, this was filtered and repeatedly washed with water, and then dried, fired, and pulverized with an airflow pulverizer to obtain an anatase-type titanium dioxide substrate. This substrate was subjected to a hydrophobic treatment in which the surface was coated with hexamethyldisilazane to obtain titanium dioxide particles.

[0083] According to the above procedure, "Titanium Dioxide 1" to "Titanium Dioxide 5" with different average primary particle sizes were produced. The average primary particle sizes of "Titanium Dioxide 1" to "Titanium Dioxide 5" are shown in Table 2 below.

[0084] [Table 2]

[0085] -First silica particles used (small silica particles)- As "small silica 1", Cabot Corporation's fumed silica product name "TG-3155F" (average primary particle size 12 nm, surface treatment agent: hexamethyldisilazane / polydimethylsiloxane) was used.

[0086] As "small silica 2", Cabot Corporation's fumed silica product name "TG-709F" (average primary particle size 18 nm, surface treatment agent: dimethyldichlorosilane) was used.

[0087] As "small silica 3", Cabot Corporation's fumed silica product name "TG-6110F" (average primary particle diameter 23 nm, surface treatment agent: hexamethyldisilazane) was used.

[0088] -Preparation of second silica particles (larger silica particles)- A stirrer, a dropping funnel, and a thermometer were set in a glass reactor, and ammonia water was added to ethanol and stirred to maintain the temperature at 20°C. Tetraethoxysilane was dropped into this solution for 60 minutes to react. After the dropwise addition, stirring was continued at 20°C for 5 hours to obtain a silica sol suspension. This silica sol suspension was heated to remove ethanol, and then toluene was added and further heated to remove water. Next, 40% by mass of hexamethyldisilazane was added to the silica particles in the suspension and reacted at 120°C for 2 hours to perform a hydrophobic treatment of the silica particles. Next, the suspension was heated to remove toluene and dried, and then coarse powder was removed using a sieve with an opening of 106 μm to obtain second silica particles "Large Silica 1" with an average primary particle diameter of 115 nm.

[0089] In addition, second silica particles with different average primary particle diameters were prepared using the same procedure and named "Large Silica 2" to "Large Silica 5." The average primary particle diameters of "Large Silica 1" to "Large Silica 5" are shown in Table 3 below. Table 3 also shows the average primary particle diameters of "Small Silica 1" to "Small Silica 3."

[0090] [Table 3]

[0091] <Production of toner and developer> [Example 1] - Toner particle production (raw material mixing, kneading, pulverization, classification process) - The following raw materials were used to prepare the toner particles. ·Binding resin Amorphous polyester resin 84% by mass Coloring agents Carbon black (manufactured by Cabot Corporation, product name: Regal 330) 6% by mass Release agent Ester wax (NOF Corporation, product name: WEP-3) 3% by mass Release agent / dispersant Styrene-acrylic copolymer resin (manufactured by Mitsui Chemicals, Inc., product name: SA800) 5% by mass Charge control agent Salicylic acid compound (manufactured by Orient Chemical Industries Co., Ltd., product name: Bontro E84) 2% by mass

[0092] The above raw materials were mixed for 5 minutes using an airflow mixer (Henschel Mixer, manufactured by Nippon Coke & Engineering Co., Ltd.). The resulting mixture was melt-kneaded in a twin-screw extruder (manufactured by Ikegai Co., Ltd., model: PCM-30) at a cylinder setting temperature of 110°C, a barrel rotation speed of 300 rpm, and a raw material supply rate of 20 kg / hour to obtain a melt-kneaded product.

[0093] The resulting molten and kneaded product was cooled on a cooling belt, then coarsely pulverized using a cutting mill, then finely pulverized using a jet pulverizer, and further classified using an air classifier to obtain "toner particles 1" having a volume average particle diameter of 6.5 μm.

[0094] - Toner production (external addition process) - (Preparation of initial toner) 100 parts by mass of the obtained "toner particle 1", 1.0 part by mass of "large silica 1", and 1.5 parts by mass of "small silica 1" were added to an air flow mixer (Nippon Coke & Engineering Co., Ltd., Henschel mixer), and the tip speed of the stirring blade was set to 40 m / sec and stirred for 2 minutes. Next, 1.0 part by mass of "fine powder 1" was added and stirred for another 2 minutes to obtain an initial toner with a volume average particle size of 6.5 μm, an adhesion strength X(Ti) of the fine powder of 84%, and an adhesion strength X(Si) of the silica particles of 78%.

[0095] (Preparation of replenishment toner) 100 parts by mass of the obtained "toner particles 1", 1.0 part by mass of "large silica 1", and 1.5 parts by mass of "small silica 1" were added to an air flow mixer (Nippon Coke & Engineering Co., Ltd., Henschel mixer), and the tip speed of the stirring blade was set to 40 m / sec and stirred for 2 minutes. Next, 1.0 part by mass of "titanium dioxide 1" was added and stirred for another 2 minutes to obtain a replenishment toner with a volume average particle size of 6.5 μm, an adhesion strength Y(Ti) of the titanium dioxide particles of 82%, and an adhesion strength Y(Si) of the silica particles of 78%.

[0096] -Preparation of two-component developer- The initial toner thus obtained was mixed with a ferrite core carrier having a volume average particle size of 40 μm, and the toner concentration relative to the total amount of the two-component developer was adjusted to 7%, to obtain a two-component developer having a toner concentration of 7%.

[0097] [Examples 2 to 36, Comparative Examples 1 to 5] As the toner particles, "toner particles 2" to "toner particles 5" were produced, each having a volume average particle diameter different from that of "toner particles 1." The volume average particle diameters of "toner particles 1" to "toner particles 5" are shown in Table 4 below.

[0098] [Table 4]

[0099] In Examples 2 to 36 and Comparative Examples 1 to 5, the toner and two-component developer were prepared in the same manner as in Example 1, except that the toner particles and external additives used in preparing the initial toner and replenishment toner were changed as shown in Tables 5 to 8 below.

[0100] [Table 5]

[0101] [Table 6]

[0102] [Table 7]

[0103] [Table 8]

[0104] [Table 9]

[0105] Tables 5 and 6 show the types, amounts added, and physical properties of the raw materials used in preparing the initial toner of the Examples and Comparative Examples. Tables 7 and 8 show the types, amounts added, and physical properties of the raw materials used in preparing the replenishment toner of the Examples and Comparative Examples. Table 9 shows the measurement results and evaluation results of the Examples and Comparative Examples.

[0106] In Examples 1 to 36, the initial toner contains fine powder and silica particles as external additives, and does not contain titanium dioxide particles or contains titanium dioxide particles at a mass content of 50% or less of the fine powder. In Examples 1 to 36, the replenishment toner contains titanium dioxide particles and silica particles as external additives, and does not contain the fine powder or contains the fine powder at a mass content of 50% or less of the titanium dioxide particles. According to Table 7, Examples 1 to 36, which satisfy these requirements, were excellent in image density and its uniformity over a long period of time, and were able to suppress the occurrence of fog.

[0107] In contrast, Comparative Examples 1 to 5, which did not satisfy these requirements, were inferior to the Examples in the evaluation results of image density, uniformity of image density, and fogging in the continuous printing test.

[0108] It can be seen that Examples 1, 3, 4, etc., in which the molar ratio of silicon atoms to titanium atoms in the fine powder is 0.03 to 1.00, are superior in the evaluation of uniformity of image density after continuous printing to Example 20, in which the molar ratio is below the lower limit. Also, it can be seen that the evaluation of image density at the beginning of printing is superior to Example 21, in which the molar ratio exceeds the upper limit.

[0109] It can be seen that Examples 1, 5, 6, etc., in which the content of fine powder per 100 parts by mass of toner particles in the initial toner is 0.3 parts by mass or more and 1.5 parts by mass or less, and the content of titanium dioxide particles per 100 parts by mass of toner particles in the replenishment toner is 0.3 parts by mass or more and 1.5 parts by mass or less, are superior in the evaluation of image density and the evaluation of uniformity of image density at the beginning of printing to Example 22, in which these contents are below the above lower limits, and are superior in the evaluation of fog to Example 23, in which these contents exceed the above upper limits.

[0110] If the content of fine powder per 100 parts by mass of toner particles in the initial toner is A parts by mass, and the content of titanium dioxide particles per 100 parts by mass of toner particles in the replenishment toner is B parts by mass, it can be seen that Examples 1 and 7, in which BA is 0.3 or less, are superior in the evaluation of uniformity of image density after continuous printing and fogging compared to Example 24, in which BA exceeds the above upper limit.

[0111] It can be seen that Examples 1, 8 to 13, etc., in which the volume average particle diameter of the toner particles in the initial toner and replenishment toner is 4 μm or more and 9 μm or less, and the average primary particle diameter of the fine powder and titanium dioxide particles in the initial toner and replenishment toner is 20 nm or more and 60 nm or less, are superior in the evaluation of uniformity of image density to Examples 25 to 30, in which these average primary particle diameters are outside the above ranges.

[0112] It can be seen that Examples 1, 14 to 16, etc., in which the silica particles contained as an external additive in the initial toner and replenishment toner are composed of first silica particles having an average primary particle diameter of 20 nm or less and second silica particles having an average primary particle diameter of 80 nm or more and 150 nm or less, are superior in the evaluation of uniformity of image density to Examples 31 to 33 in which the average primary particle diameter of the first or second silica particles is outside the above range.

[0113] It can be seen that Examples 1, 17, 18, etc., in which the content of silica particles per 100 parts by mass of toner particles in the initial toner is 1.5 parts by mass or more and 3.0 parts by mass or less, and the content of silica particles per 100 parts by mass of toner particles in the replenishment toner is 1.5 parts by mass or more and 3.0 parts by mass or less, are superior in the evaluation of uniformity of image density and fogging after continuous printing to Example 34, in which the content of silica particles is less than the lower limit. It can also be seen that they are superior in the evaluation of fogging after continuous printing to Example 35, in which the content of silica particles exceeds the upper limit.

[0114] In the initial toner, if the adhesion strength of the fine powder and titanium dioxide particles to the toner particles is X(Ti) and the adhesion strength of the silica particles to the toner particles is X(Si), then X(Si) / X(Ti) is 1.1 or less, and in the replenishment toner, if the adhesion strength of the fine powder and titanium dioxide particles to the toner particles is Y(Ti) and the adhesion strength of the silica particles to the toner particles is Y(Si), then Y(Si) / Y(Ti) is 1.1 or less. It can be seen that Examples 1, 19, etc., in which X(Si) / X(Ti) and Y(Si) / Y(Ti) exceed the above upper limits, are superior in the evaluation of fog after continuous printing.

[0115] The embodiments disclosed herein are illustrative in all respects and are not intended to be limiting. Therefore, the technical scope of the present disclosure is not interpreted solely by the above-described embodiments, but is defined based on the claims. Also, all modifications within the scope and meaning equivalent to the claims are included. [Explanation of symbols]

[0116] 1 Toner particles 2. Secondary silica particles (large-diameter silica particles) 3. First silica particles (small silica particles) 4. Fine powder made by adding silica to strontium titanate and hydrophobizing the surface of the core with a silane compound 11 General toner particles 12 General large particle size silica particles 13 Typical small particle size silica particles 15 General charge control agents C Career T1 Initial Toner T2 Refill Toner T11 General low charge toner T12 General high charge toner

Claims

1. An image forming apparatus in which a two-component developer composed of an initial toner and a carrier is filled in a developing tank in advance, and a replenishment toner is replenished into the developing tank as development is performed, The initial toner and the replenishment toner are toner particles having an external additive attached to the surface thereof, the initial toner contains, as an external additive, a fine powder in which a core formed by adding silica to strontium titanate and the surface of which is hydrophobized with a silane compound, and silica particles, and does not contain titanium dioxide particles or contains titanium dioxide particles in a mass content of 50% or less of the fine powder; The image forming apparatus according to the present invention is characterized in that the replenishment toner contains titanium dioxide particles and silica particles as external additives, and does not contain the fine powder or contains the fine powder in a mass content of 50% or less of the titanium dioxide particles.

2. 2. The image forming apparatus according to claim 1, 13. An image forming apparatus according to claim 12, wherein the molar ratio of silicon atoms to titanium atoms in said fine powder is from 0.03 to 1.

00.

3. 3. The image forming apparatus according to claim 1, the content of the fine powder relative to 100 parts by mass of toner particles in the initial toner is 0.3 parts by mass or more and 1.5 parts by mass or less; 2. An image forming apparatus comprising: a supply toner having a content of titanium dioxide particles in the supply toner of 0.3 parts by mass or more and 1.5 parts by mass or less per 100 parts by mass of toner particles.

4. 3. The image forming apparatus according to claim 1, The image forming apparatus is characterized in that, when the content of the fine powder per 100 parts by mass of toner particles in the initial toner is A parts by mass, and the content of titanium dioxide particles per 100 parts by mass of toner particles in the replenishment toner is B parts by mass, B-A is 0.3 or less.

5. 3. The image forming apparatus according to claim 1, the volume average particle diameter of the toner particles in the initial toner and the replenishment toner is 4 μm or more and 9 μm or less; an average primary particle diameter of the fine powder and titanium dioxide particles in the initial toner and the replenishment toner is 20 nm or more and 60 nm or less;

6. 3. The image forming apparatus according to claim 1, The image forming apparatus is characterized in that the silica particles contained as an external additive in the initial toner and the replenishment toner are composed of first silica particles having an average primary particle diameter of 20 nm or less and second silica particles having an average primary particle diameter of 80 nm or more and 150 nm or less.

7. 3. The image forming apparatus according to claim 1, the content of silica particles in the initial toner is 1.5 parts by mass or more and 3.0 parts by mass or less with respect to 100 parts by mass of toner particles, The image forming apparatus according to the present invention is characterized in that the content of silica particles in the replenishment toner is 1.5 parts by mass or more and 3.0 parts by mass or less with respect to 100 parts by mass of toner particles.

8. 3. The image forming apparatus according to claim 1, In the initial toner, the adhesion strength of the fine powder and titanium dioxide particles to the toner particles is X(Ti), and the adhesion strength of the silica particles to the toner particles is X(Si), where X(Si) / X(Ti) is 1.1 or less; An image forming apparatus characterized in that, in the replenishment toner, the adhesion strength of the fine powder and titanium dioxide particles to the toner particles is Y(Ti), and the adhesion strength of the silica particles to the toner particles is Y(Si), where Y(Si) / Y(Ti) is 1.1 or less.

Citation Information

Patent Citations

  • Developing method

    JP1996314280A